Peran Guru Pendidikan Agama Islam dalam Membentuk Resiliensi Siswa di SMA Negeri 1 Dayeuhluhur Kabupaten Cilacap - Rachmawati, Defi; Wanojaleni, Kartika (Prodi Pendidikan Agama Islam IAINU Kebumen, 2022)
The purpose of this study was to find out the role of Islamic Religious Education teachers in building student resilience at SMA Negeri 1 Dayeuhluhur, Cilacap Regency. The findings in this study are that the problems experienced by students are parental divorce, economic difficulties, and broken homes, student resilience is at a normal or average level. the biggest factors forming student resilience are parents or family, personal self, and peers, Islamic Religious Education teachers have a role in shaping the resilience of students of SMA Negeri 1 Dayeuhluhur (1) as mentors, through the application of spiritual values in habituation activities dhuha prayer, tadarus, literacy, weekly infaq which is implemented at Dayeuhluhur 1 Public High School. (2)as a role model and (3) as a motivator, which is carried out by Islamic Religious Education teachers when learning is in progress, while Islamic Religious Education materials that encourage the formation of student resilience include self-control (Mujahadah Al Nafsi), faith in Allah SWT., and ethics in Muslim/Muslim clothing.